A PERSPECTIVE STUDY ON PANCHAYATI RAJ INSTITUTIONS (With reference: Women Empowerment) - Viriti Danteswara Rao (Galaxy International Interdisciplinary Research Journal, 2023)
Empowerment is a process that enables women to gain access to and control of material, intellectual and human resources. Empowerment is the redistribution of power that challenges patriarchal ideology and male dominance. Political empowerment of women is part of the overall empowerment process. Political participation is a major path to women’s empowerment and participation in decision-making power will lead to women’s empowerment in true sense of the term. In other words, increased decision-making power gives greater ability to influence matters that affect our lives in the community and the society at large. present study analyzed the Badangi mandal Panchayat in Vijayanagarm District in Andhra Pradesh.